DINAMISITAS PENDEKATAN SUFISME DALAM WACANA PENAFSIRAN AL-QUR’AN - Musyfiqur Rosyi; Abd. Basid; Moh. Asy'ari Muthhar (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract The Sufistic tradition is a significant aspect of Islamic civilisation's history and a new direction in Qur'anic interpretation methodology. The epistemology developed by the Sufis for interpreting the Qur'an is closely tied to the symbolism of the holy verses, which metaphorically presented as the sacred soul's orientation towards God. The Sufis interpret the verses by delving into their meaning with doctrines and spiritual experiences, going beyond the text's literal meaning. This style of interpretation represents a distinct variation in the field of interpretation. It becomes two variants, namely nadzari and isyari. The author aims to show how the Sufi paradigm affects the interpreting world. The discourse surrounding Sufi interpretation and its development over time will be explored. This research aims to reveal, unravel, and trace the growth of the discourse of interpretation throughout history using the historical analytical method and literature references. The study concludes that the natural Sufi figures interpret the Qur'an by synchronising it with their received signals, focusing on 'al-ahwal' and 'al-maqamat', commonly known as: 'tasawuf stations.' The phenomenon of Sufi interpretation is noteworthy due to the variety of responses it elicits, both supportive and critical. It is important to note that the trend of Sufism studies must impact the realm of Qur'anic interpretation, as the Qur'an will continue to be the focus of attention and research in the development of science. Keywords: Sufism, Quranic Interpretation